Infections in gynecology and obstetrics. Sexually transmitted infections. - Maradiegue, Eduardo (2015)
Sexually transmitted infections are a group of diseases whose transmission is performed at the time of intercourse. We describe them according to their etiology, or those caused by viruses, bacteria, chlamydia, spirochetes, protozoa and fungi. There are parasites that are transmitted through body contact during sex, such as produced by pubic lice or pubic Phithirus acarosis by Sarcoptes scabiei variety hominis, which will not be described in this paper.